2020
DOI: 10.1101/2020.03.09.984690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the effect of glycaemic traits on the risk of psychiatric illness using Mendelian randomisation

Abstract: Data from observational studies have suggested an involvement of abnormal glycaemic regulation in the pathophysiology of psychiatric illness. This may be an attractive target for clinical intervention as glycaemia can be modulated by both lifestyle factors and pharmacological agents. However, observational studies are inherently confounded, and therefore causal relationships cannot be reliably established. We employed genetic variants rigorously associated with three glycaemic traits (fasting glucose, fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(75 reference statements)
1
1
0
Order By: Relevance
“…Exploring further the genetic links between these neuropsychiatric disorders and glycaemic traits linked to insulin resistance, we revealed a novel positive correlation between ADHD and FPG, as well as negative bivariate correlations between AN and both FPI and HOMA-IR that replicate and update previous findings [29,46]. A Mendelian randomisation study had also previously shown that higher levels of FPI have a causal effect in reducing the risk of AN [51].…”
Section: Table 2 Genetic Correlation Table Reporting the Detailed Res...supporting
confidence: 84%
“…Exploring further the genetic links between these neuropsychiatric disorders and glycaemic traits linked to insulin resistance, we revealed a novel positive correlation between ADHD and FPG, as well as negative bivariate correlations between AN and both FPI and HOMA-IR that replicate and update previous findings [29,46]. A Mendelian randomisation study had also previously shown that higher levels of FPI have a causal effect in reducing the risk of AN [51].…”
Section: Table 2 Genetic Correlation Table Reporting the Detailed Res...supporting
confidence: 84%
“…Exploring further the genetic links between these neuropsychiatric disorders and glycaemic traits linked to insulin resistance, we revealed a novel positive correlation between ADHD and FGlu, as well as negative bivariate correlations between AN and both FIns and HOMA-IR that replicate and update previous findings (32, 42). A Mendelian randomisation study had also previously shown that higher levels of FIns have a causal effect in reducing the risk of AN (47).…”
Section: Discussionmentioning
confidence: 91%